Cross-Sectional and Longitudinal Associations between Subjective Sleep Difficulties and Self-Perceptions of Aging. Issue 6 (2nd November 2022) - Sabatini, Serena; Ukoumunne, Obioha C; Ballard, Clive; Collins, Rachel; Corbett, Anne; Brooker, Helen; Clare, Linda
ABSTRACT: Background: Only one study has explored the associations of subjective sleep difficulties with self-perceptions of aging. It focused on a global indicator of self-perceptions of aging (subjective age) despite individuals reporting different experiences of aging in relation to different life domains. The concept of awareness of negative age-related change, capturing perceived losses across five domains (e.g., physical health, cognition), may be more appropriate when relating subjective sleep difficulties to self-perceptions of aging. We examined whether nine different indicators of subjective sleep difficulties predict levels of awareness of negative age-related change and subjective age, measured concurrently and one year later, while controlling for covariates (mood and daily function). Participants/Methods: We used data from the PROTECT cohort study; 4, 482 UK residents (mean age = 66.1; SD = 6.9) completed measures of awareness of age-related change, subjective age, mood, daily function, and subjective sleep difficulties. Results: Based on linear regression analyses, poorer quality of sleep, lower alertness after awakening, satisfaction with sleep, depth of sleep, more frequent early awakening, difficulty falling asleep, more times awake during a night, fewer hours of sleep during the night and more hours of sleep during the day predicted higher awareness of negative age-related change at baseline and follow-up ( p < .001). Associations were small in size. Associations between subjective sleep difficulties and subjective age were either negligible or statistically non-significant. Conclusions: Although subjective sleep difficulties are one of the many factors associated with awareness of negative age-related change, addressing sleep difficulties, alongside negative mood, and poor daily functioning, may promote a small additional increase in positive self-perceptions of aging.